Study and Application of Similar Material Ratio in Collapsible Loess - Bingchao Zhao; Yunxiang Ma; Yaxin Guo; Hao Sun; Jingbin Wang; Hailong Wang (Advances in Materials Science and Engineering)
The similar material of collapsible loess is the basis and premise of the experimental study on the surface movement and deformation law of coal seam mining in collapsible loess-covered areas. The orthogonal experiment is used to make up similar material with different proportions using river sand and barite powder as aggregate, clay and gypsum as cementing material, and diatomite as adjusting material. The reasonable proportion of similar material in collapsible loess is studied by using range analysis, similar simulation, and field measurement. The results show that the content of diatomite plays a leading role in the collapsibility coefficient of similar material, and the collapsibility coefficient is positively correlated with the content of diatomite; moisture content is the main control of the cohesion of the material, and cohesion is negatively correlated with the moisture content; the ratio of bone-to-glue has the most significant effect on the internal friction angle, and the internal friction angle is positively correlated with the ratio of bone-to-glue. The reasonable ratio of the similar material in collapsible loess is 8 : 2 of the ratio of bone-to-glue, the ratio of clay-to-gypsum is 9 : 1, the barite powder content is 6%, the diatomite content is 23%, and the moisture content is 13%, and the mechanical parameters of the collapsible loess are 5.3%–6.3% different from the target value of similar material through laboratory tests, which can meet the experimental requirements. It is verified by a similar simulation experiment that the maximum surface subsidence value and the surface fracture width in the simulation results are 6.9% and 7.8% different from the field measured results, indicating a high degree of agreement. The results of the study have important references and guiding significance for the preparation of similar material with similar models.